2022
DOI: 10.2340/jrm.v54.2203
|View full text |Cite
|
Sign up to set email alerts
|

Referrals to Early Specialized Rehabilitation after Traumatic Brain Injury during the Covid-19 Pandemic

Abstract: Objective: To quantify potential changes in direct referral to early specialized rehabilitation during the COVID-19 pandemic and the injury pattern of patients hospitalized with traumatic brain injury (TBI) at a level 1 trauma centre.Methods: In this registry-based study, data were retrieved from the Oslo TBI Registry-Neurosurgery and included adult patients with injury-related intracranial findings admitted to Oslo University Hospital (OUH). The study focused on a period of time when OUH was in any level of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We assume that this effect was most pronounced for specialized rehabilitation, with the possibility of underestimating the proportion of patients discharged under non-pandemic circumstances. However, a study performed at OUH that looked at the period from March 2020 to August 2021 found that for patients with moderate-to-severe TBI, the direct pathway to early specialized rehabilitation was maintained (Tverdal et al 2022 ). Dropout analysis (non-responders or declined participation) revealed no significant differences in sex or mean age between the dropouts and the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that this effect was most pronounced for specialized rehabilitation, with the possibility of underestimating the proportion of patients discharged under non-pandemic circumstances. However, a study performed at OUH that looked at the period from March 2020 to August 2021 found that for patients with moderate-to-severe TBI, the direct pathway to early specialized rehabilitation was maintained (Tverdal et al 2022 ). Dropout analysis (non-responders or declined participation) revealed no significant differences in sex or mean age between the dropouts and the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was not a global response; in other parts of the world rehabilitation services were deemed more of a priority. A registry-based study from Norway, including 1310 hospitalized patients with traumatic brain injury (TBI), demonstrated that the direct pathway to early specialized rehabilitation was maintained during 2020–2021 ( 38 ). Similarly, while Japan commonly follows the recommendations of the CDC and WHO, the Japanese government and the leading Medical Rehabilitation Organization did not recommend early discharge from the hospital ( 39 , 40 ).…”
Section: Responses To Covid-19 Across the Globementioning
confidence: 99%
“…Literature pertaining to the impact of the COVID-19 pandemic on TBI rehabilitation profiles and outcomes are unknown, in particular in regards Asian TBI [17]. We aimed to study the effects of the COVID-19 pandemic on inpatient TBI case-mix and rehabilitation outcomes by comparing two unique cohorts from similar duration pre and post pandemic periods.…”
Section: Introductionmentioning
confidence: 99%